2019
DOI: 10.1177/0300060519893166
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of extravasation on ruptured uterine artery pseudoaneurysm using contrast-enhanced ultrasonography during uterine balloon tamponade

Abstract: Objective Contrast-enhanced ultrasonography (CEU) has been used in critical trauma situations to visualize extravasation; however, its use is limited in the field of obstetrics. Cases of ruptured uterine artery pseudoaneurysm (UAP) were analyzed to clarify the efficacy to CEU during uterine balloon tamponade. Methods Cases of ruptured UAP diagnosed at a teaching university hospital from January 2015 to December 2017 were retrospectively analyzed. UAP was diagnosed using color Doppler ultrasonography. Extravasa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
1
6
0
1
Order By: Relevance
“…We also reported cases of UBT using ultrasound contrast agents for pseudoaneurysms. 17) As with the present case, we reported in that study that bleeding points can be identified and reliable hemostasis can be achieved with UBT. Another advantage of this method is that intrauterine evacuation can be performed without technical restrictions and hemostasis can be achieved in a shorter time and at a lower cost relative to hysteroscopy or UAE.…”
Section: Discussionsupporting
confidence: 82%
“…We also reported cases of UBT using ultrasound contrast agents for pseudoaneurysms. 17) As with the present case, we reported in that study that bleeding points can be identified and reliable hemostasis can be achieved with UBT. Another advantage of this method is that intrauterine evacuation can be performed without technical restrictions and hemostasis can be achieved in a shorter time and at a lower cost relative to hysteroscopy or UAE.…”
Section: Discussionsupporting
confidence: 82%
“…Further, several case reports have mentioned the use of uterine balloon tamponade and laparoscopic surgery for the treatment of UAP. [ 11 , 12 ] Treatment options have therefore evolved from surgery to TAE, which is safe and effective in recent years especially for patients who desire fertility preservation. The surgical approach may be more suitable in cases of acute and massive bleeding when there is no time for TAE.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, the main choice of treatment for UAP was open surgical management, including hysterectomy and ligation of uterine or internal iliac artery. Further, several case reports have mentioned the use of uterine balloon tamponade and laparoscopic surgery for the treatment of UAP [11,12] . Treatment options have therefore evolved from surgery to TAE, which is safe and effective in recent years especially for patients who desire fertility preservation.…”
Section: Discussionmentioning
confidence: 99%
“…However, invasive procedures have the potential to decrease fertility 4 ; therefore, measures to prevent balloon prolapse are important. 5,6 In 2011, Jain described the concept of the method of cerclage with IBT. 7 Here, we secondary describe a case of cervical cerclage with IBT for placenta previa that involved cervical dilation and we discuss the effect of IBT with cervical cerclage.…”
mentioning
confidence: 99%